2021
DOI: 10.3390/jof7030207
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Identifying Fungal Kingdom Enzyme Hotspots from Genome Sequences

Abstract: Fungal genome sequencing data represent an enormous pool of information for enzyme discovery. Here, we report a new approach to identify and quantitatively compare biomass-degrading capacity and diversity of fungal genomes via integrated function-family annotation of carbohydrate-active enzymes (CAZymes) encoded by the genomes. Based on analyses of 1932 fungal genomes the most potent hotspots of fungal biomass processing CAZymes are identified and ranked according to substrate degradation capacity. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
(75 reference statements)
0
3
0
1
Order By: Relevance
“…Compared to EcM fungi, the role of DSE fungi in soil organic matter decomposition is less known. Dark septate endophytes may be relatively efficient degraders of organic matter due to their expanded repertoire of CAZymes, including plant cell wall degrading enzymes 62 , 63 . We found that DSE colonization positively associated with soil fungal CAZyme diversity and influenced their composition.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to EcM fungi, the role of DSE fungi in soil organic matter decomposition is less known. Dark septate endophytes may be relatively efficient degraders of organic matter due to their expanded repertoire of CAZymes, including plant cell wall degrading enzymes 62 , 63 . We found that DSE colonization positively associated with soil fungal CAZyme diversity and influenced their composition.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in sequence read proportions of fungi in the basidiomycete genus Mycena (order Agaricales) toward summer in petioles from both the healthy and diseased stand is noteworthy. For basidiomycetes, some species of Mycena have an astonishingly potent carbohydrate active enzyme portfolio on all plant cell wall components (Lange et al, 2021), something that may enable plasticity in feeding on different cell wall carbohydrates according to substrate properties and phase of decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pathogenic Diaporthe species have been recognized as plant growth promoters ( Vázquez de Aldana et al, 2021 ; da Silva Santos et al, 2022 ; Toghueo et al, 2022 ), and biocontrol agents ( Marak et al, 2002 ; Dos Santos et al, 2016 ; Dini-Andreote, 2020 ; Abramczyk et al, 2022 ). From an industrial and pharmaceutical point of view, they are well-known producers of enzymes ( Lange et al, 2021 ; Baluyot et al, 2022 ) and secondary metabolites exhibiting a wide range of activities including antimicrobial, antiviral, antioxidant, anti-inflammatory and anticancer ( Chepkirui and Stadler, 2017 ; Xu et al, 2021 ). Therefore, studies aiming to analyze and better characterize Diaporthe species are of interest, particularly to fully comprehend not only their role as ubiquitous species in nature, but also their potential as metabolite producers, plant growth promoters, biocontrol agents, or for control measures in case of potential pathogenicity.…”
Section: Introductionmentioning
confidence: 99%